Bacterial sensitivity in patients with urinary infections Barquisimeto, Lara. January - june 2017 (Revista Venezolana de Salud Pública, 2018)
Urinary infections frequently presents recurrences, justifying repeated treatments that can lead to bacterial resistance, which has become a public health problem. The objective of this work is to determine the sensitivity patterns of bacterial strains isolated from patients with mild urinary tract infection in Barquisimeto, Lara state in the period January - July 2017. This is a quantitative, descriptive and transversal research. The universe consisted of 715 patients with suspected urinary infection. The sample selected was 525 patients who attended the clinic of the Cooperativa Cecosesola. Samples were processed according to CLSI procedures for culture and antibiogram. The results were analyzed with the Microsoft Excel 2010 program. In 33% (175) of the samples, bacterial growth was obtained. The female gender predominated in 85% of the samples analyzed. The results obtained indicated that the isolated bacterial strains were Escherichia coli (75%), Enterobacter cloacae (10%), Proteus species (7%), Klebsiella pneumoniae (4%), Pseudomonas aeruginosa (2%) and others (2%; cocos Gram Positives and Candida spp). 85% of the strains of E. coli were sensitive to quinolones, 80% to aminoglycosides, 75% to nitrofurantoin, 50% to trimethoprim sulfate and only 40% to cephalexin. The data obtained indicates that antimicrobials useful in the treatment of urinary tract infections in the study population are quinolones, aminoglycosides and nitrofurantoin as a third option.
Keywords: Venezuela; urinary infection; antibiotics